Comparison of Clinical Outcomes of Two-Level PELD and Foraminoplasty PELD for Highly Migrated Disc Herniations: A Comparative Study. (13th October 2019) - Wu, Xinbo; Fan, Guoxin; He, Shisheng; Gu, Xin; Yang, Yunfeng
Abstract : Objective . The aim of this study is to compare the clinical outcomes of two-level percutaneous endoscopic lumbar discectomy (PELD) and foraminoplasty PELD in treating highly migrated lumbar disc herniations. Methods . Patients with highly migrated lumbar disc herniations were enrolled from May 2014 to June 2016. Low back pain and leg pain were evaluated by the Visual Analog Scale (VAS), and functional outcomes were assessed with the Oswestry Disability Index (ODI). The satisfaction rate of clinical outcomes was assessed according to the modified MacNab criteria. In addition, the intraoperative duration and postoperative complications were also recorded. Results . Forty patients, 14 cases in two-level PELD group and 26 cases in foraminoplasty PELD group, were included. The VAS scores of low back pain (P = 0.67 ) and leg pain (P = 0.86 ), as well as the ODI scores (P = 0.87 ), were comparative between two-level PELD and foraminoplasty PELD groups. The satisfaction rate of clinical outcomes based on the modified MacNab criteria in the two-level PELD group was equivalent to that in foraminoplasty PELD group (92.9% versus 92.3%, P = 0.92 ). In addition, the intraoperative duration of two-level PELD group was longer than that of foraminoplasty PELD group (80.2 ± 6.6 min versus 64.1 ± 7.3 min, P < 0.01 ). The postoperative complications in the two-level PELD group (postoperative dysesthesia: N = 1) were relatively fewer as compared to those in the foraminoplasty PELD group (postoperative dysesthesia: N = 1; recurrence: N = 1; nucleus pulposus residues: N = 1). Conclusions . Both two-level PELD and foraminoplasty PELD are safe and effective surgical procedures for the patients with highly migrated lumbar disc herniations. Moreover, the two-level PELD technique has merits in reducing the incidence of postoperative nucleus pulposus residue.